Heat shock protein 90 inhibitor RGRN-305 potently attenuates skin inflammation - Ben Abdallah, Hakim; Seeler, Sabine; Bregnhøj, Anne; Ghatnekar, Gautam; Kristensen, Lasse S.; Iversen, Lars; Johansen, Claus (Frontiers in Immunology, 2023)
Introduction Chronic inflammatory skin diseases may have a profound negative impact on the quality of life. Current treatment options may be inadequate, offering an unsatisfactory response or side effects. Therefore, ongoing efforts exist to identify novel effective and safe treatments. Heat shock protein (HSP) 90 is a chaperone that promotes the activity of a wide range of client proteins including key proinflammatory molecules involved in aberrant inflammation. Recently, a proof-of-concept clinical trial of 13 patients suggested that RGRN-305 (an HSP90 inhibitor) may be an oral treatment for psoriasis. However, HSP90 inhibition may be a novel therapeutic approach extending beyond psoriasis to include multiple immune-mediated inflammatory skin diseases. Methods This study aimed to investigate (i) the anti-inflammatory effects and mechanisms of HSP90 inhibition and (ii) the feasibility of topical RGRN-305 administration (new route of administration) in models of inflammation elicited by 12-O-tetradecanoylphorbol-13-acetate (TPA) in primary human keratinocytes and mice (irritative dermatitis murine model). Results/Discussion In primary human keratinocytes stimulated with TPA, a Nanostring® nCounter gene expression assay demonstrated that HSP90 inhibition with RGRN-305 suppressed many proinflammatory genes. Furthermore, when measured by quantitative real-time polymerase chain reaction (RT-qPCR), RGRN-305 significantly reduced the gene expression of TNF, IL1B, IL6 and CXCL8. We next demonstrated that topical RGRN-305 application significantly ameliorated TPA-induced skin inflammation in mice. The increase in ear thickness (a marker of inflammation) was significantly reduced (up to 89% inhibition). In accordance, RT-qPCR of the ear tissue demonstrated that RGRN-305 robustly reduced the gene expression of proinflammatory markers (Tnf, Il1b, Il6, Il17A and Defb4). Moreover, RNA sequencing revealed that RGRN-305 mitigated TPA-induced alterations in gene expression and suppressed genes implicated in inflammation. Lastly, we discovered that the anti-inflammatory effects were mediated, at least partly, by suppressing the activity of NF-κB, ERK1/2, p38 MAPK and c-Jun signaling pathways, which are consistent with previous findings in other experimental models beyond skin inflammation. In summary, HSP90 inhibition robustly suppressed TPA-induced inflammation by targeting key proinflammatory cytokines and signaling pathways. Our findings suggest that HSP90 inhibition may be a novel mechanism of action for treating immune-mediated skin disease beyond psoriasis, and it may be a topical treatment option.